The effectiveness of mI SMART: A nurse practitioner led technology intervention for multiple chronic conditions in primary care - Jennifer A. Mallow; Laurie A. Theeke; Elliott Theeke; Brian K. Mallow (Elsevier, 2018)
Aims: Used as integrated tools, technology may improve access and outcomes of care. A new intervention that integrates multiple technologies called mI SMART has been developed, implemented, and evaluated by Nurse Practitioners. The aim of this paper is to present the initial effectiveness of a web-based, structure of sensors and mobile devices designed to overcome the known health determinant of access to care for rural, chronically ill patients by using technology. Methods: The study was conducted at a community primary-care clinic that provides free healthcare to impoverished adults. Adults with at least one chronic condition, a minimum of 3rd grade reading level, and without dementia/psychosis were recruited. Participants were given a Nexus7 tablet and Bluetooth self-monitoring devices. The intervention lasted for 12 weeks. Blood glucose, blood pressure, and weight were collected using the provided Bluetooth devices and means were evaluated with paired-samples t-tests before and after the intervention. Results: Thirty participants were majority female, white, married, high-school educated or less, earning less than $20,000 per annum, and had multiple chronic conditions. Pre-intervention glucose, systolic blood pressure, diastolic blood pressure, weight and Body Mass Index were all reduced after the 12-week intervention. Conclusions: The mI SMART intervention is efficacious for use in improvised adults living in rural areas with multiple chronic conditions. As previously reported, the intervention was also shown to be feasible and acceptable to patients. The next step is a larger randomized controlled trial. Keywords: Health disparities, mHealth, Multiple chronic conditions, Nursing informatics, Rural